Clinical characterization and outcome of prolonged heart rate-corrected QT interval among children with syndactyly. Issue 42 (16th October 2020) - Han, Hao; Chen, Youzhou; Li, Songnan; Ren, Lan; Zhang, Jianqiang; Sun, Huayi; Dong, Jianzeng; Zhao, Xingshan
Abstract : Abstract: Prolonged heart rate-corrected QT (QTc) interval is an independent risk factor for sudden cardiac death, which is the hallmark of Timothy syndrome (TS). There are little data on children with syndactyly and QTc prolongation. To evaluate the characteristics and long-term outcomes in children with syndactyly, and to attempt to identify TS in patients with syndactyly and QTc prolongation. This is a retrospective case-control study of children with syndactyly who visited Beijing Jishuitan Hospital between July 2003 and February 2013. The patients with prolonged QTc intervals are matched 1:4 with patients without prolongation. Genetic testing of the CACNA1C gene is routinely performed in patients with QTc prolongation. The mean age at admission is 3.4 ± 2.3 years. Compared with the normal QTc group, those with QTc prolongation showed higher frequencies of congenital heart disease (11.8% vs 1.5%, P  = .042), mental retardation and facial dysmorphia (11.8% vs 0, P  = .004), and T wave alternans (23.5% vs 4.4%, P  = .01). In the multivariable analysis, only T wave alternans (OR = 10.61, 95%CI: 1.39–81.16, P  = .023) is independently associated with QTc prolongation in patients with syndactyly. One child with QTc prolongation had a mutation in the CACNA1C gene. No patients with prolonged QTs interval met the threshold for TS. Children with syndactyly and prolonged QTc interval had more multisystem diseases and electrocardiography abnormalities. T wave alternans is independently associated with QTc prolongation in patients with syndactyly.